University Curricula and Student Movement in Indonesia: “Gejayan Memanggil” Protest in Yogyakarta - Amalinda Savirani (Universitas Sultan Ageng Tirtayasa, 2023)
Student movements have played a significant political role in many countries in Asia, including Indonesia. They have been labeled